Implementasi Augmented Reality Pada Aplikasi Pengenalan Komponen Pesawat Terbang - Denny Riandhita Arief Permana (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
The development of information and communication technology hasimproved, and has covered various areas of humanlife, and made access to information very easy, and educational learning media is increasingly varied from conventional to book, some with video, voice or Augmented Reality (AR) technology. Mobile communication technology has now grown very rapidly. Along with these developments, there is a change in people's point of view so that people now utilize mobile communication technology not only as a means of communication, but also as a tool to find a variety of information, and news. AR technology has been developed on android smartphones. Smartphones with andorid operating system have many advantages, many android platforms are open source (open) for developers to create applications. flight to increase the interest in learning and improve the value of understanding the structure of the aircraft to know in terms of the interior to the body of the aircraft until it becomes an effective, interesting and educational application to use.